Find the equation for the line containing the points (-2, -5) and (6, 3).
y = 2x - 3,
y = -2x - 3,
y = x + 3,
y = x - 3

Question

Asked 4/3/2014 6:41:52 AM

Updated 4/3/2014 7:16:35 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [4/3/2014 7:14:46 AM]

andrewpallarca|Points 34564|

Question

Asked 4/3/2014 6:41:52 AM

Updated 4/3/2014 7:16:35 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [4/3/2014 7:14:46 AM]

Rating

3

The equation for the line containing the points (-2, -5) and (6, 3) is y = x - 3

Added 4/3/2014 7:16:35 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/4/2014 1:40:58 PM]

Solve x 2 + 2x - 1 = 0
**Weegy:** (x) = 4^2x - 100 when x = 2 f(x) = 4^2(2) - 100 f(x) = 16(2) - 100 f(x) = 32 - 100 f(x) = -68 **User:** What type of conic section is the following equation?
9x2 + 4y2 - 36 = 0
parabola,
circle,
hyperbola,
ellipse (More)

Question

Not Answered

Updated 4/21/2014 9:22:43 PM

2 Answers/Comments

x^2 + 2x - 1 = 0

a = 1, b = 2, c = -1

b^2 - 4ac = 2^2 - 4(1)(-1) = 8

x = [-2 ± sqrt(8)]/2

= -1 ± sqrt(2)

The solution for the equation x^2 + 2x - 1 = 0 is x = -1 + sqrt(2) or x = -1 - sqrt(2)

a = 1, b = 2, c = -1

b^2 - 4ac = 2^2 - 4(1)(-1) = 8

x = [-2 ± sqrt(8)]/2

= -1 ± sqrt(2)

The solution for the equation x^2 + 2x - 1 = 0 is x = -1 + sqrt(2) or x = -1 - sqrt(2)

Added 4/21/2014 9:19:47 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/21/2014 9:21:29 PM]

Select the conic section that represents the equation.
20x = 4y 2
parabola,
circle,
hyperbola,
ellipse

Question

Not Answered

Updated 4/21/2014 8:43:04 PM

1 Answer/Comment

Find the sum and product of the roots.
2x 2 + 6x - 8 = 0 **Weegy:** The simpified equation is (B) 6x+ 7. (More)

Question

Expert Answered

Updated 4/3/2014 7:32:32 AM

1 Answer/Comment

2x^2 + 6x - 8 = 0

2(x^2 + 3x - 4) = 0

2(x + 4)(x - 1) = 0

x = -4 or 1

The sum of the roots = -4 + 1 = -3

The product of the roots = (-4)(1) = -4

2(x^2 + 3x - 4) = 0

2(x + 4)(x - 1) = 0

x = -4 or 1

The sum of the roots = -4 + 1 = -3

The product of the roots = (-4)(1) = -4

Added 4/3/2014 7:32:32 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/3/2014 7:35:48 AM]

If f = {(-1, 0), (-2, 2), (-3, 4), (-4, 6), (-5, 8)}, what is the range?
{-1, -2, -3, -4, -5},
integers,
even numbers,
{0, 2, 4, 6, 8}

Question

Not Answered

Updated 4/3/2014 8:27:24 PM

1 Answer/Comment

One number is five times another number. Their sum is 42. What are the two numbers?
5 and 25
7 and 35
6 and 36
8 and 34

Question

Not Answered

Updated 4/19/2014 3:07:06 PM

1 Answer/Comment

27,959,633

questions answered

There are no comments.